PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN MAHASISWA UNIVERSITAS PAKUAN DALAM MEMILIH RUMAH KOST - . Susilowati (Jurnal Komunikasi, 2015)
Increasing number of students who have graduated from high school or vocational high school sought to continue their study to public or private colleges, both in the city and outside the city. For students who leave the area or hometown and settle in the region or city where the university stands, require the services of boarding house. To study the problem above, this research engages 7P Marketing Mix Approach, namely, Product, Place, Process, People, Promotion, Physical Evidence, Price. The purpose of this research is to analyze and examine the simultaneously and partially marketing mix influence which includesproducts (services of boarding houses), price, place, promotion, people, physical facilities and process against the decision of Pakuan Bogor University students in choosing a boarding house. The Engineering students of Pakuan Bogor University generation of 2015 who have used the services of boarding houses in the area around KPP Housing IPB, Tegallega district, Bogor, become the population of this research. Total samples are 32 respondents as the users of boarding house services, using non-probability sampling technique, that is purposive sampling method. The results showed that the Product (products / services boarding house), Price (the price), Place (place), phisycal Evidence (physical facilities) and Proces (process) significantly influence the purchase decision. As for the Promotion (promotion), and People (people) do not significantly affect (Y), and they have a significant influence on the purchase decision simultaneously.Keywords: marketing mix, purchasing decisions